Public Policy Responses to Address the Mental Health Consequences of the COVID-19 Pandemic: Evidence From Chile - Irarrazaval, Matias; Norambuena, Pablo; Montenegro, Cristian; Toro-Devia, Olga; Vargas, Belen; Caqueo-Urízar, Alejandra (Frontiers in Public Health, 2021)
Objectives: This paper reviews the mental health policies that have been implemented in Chile in response to the COVID-19 pandemic and the international context of countries' responses. Even before the start of the pandemic, there were significant barriers to access mental health services in Chile, coupled with a scenario of nationwide social unrest and protests that questioned the legitimacy of public institutions; now the rapidly worsening outbreaks of COVID-19 are exacerbating the pre-existing mental health crisis. Methods: We conducted a bibliometric and content analysis of the Chilean mental health public policies implemented during the COVID-19 pandemic and then compared these policies with international experiences and emerging scientific evidence on the mental health impact of pandemics. Results: Our analysis of the policies identifies five crucial points of action developed in Chile: (i) an established framework to address mental health in emergency and disaster situations; (ii) a timely COVID-19 Mental Health Action Plan; (iii) inclusion of mental health in the public health agenda; (iv) development of a presidential strategy during the pandemic for comprehensive mental health and well-being; and (v) emerging research assessing the mental health implications of COVID-19. Conclusions: In Chile, the public policy responses to address the mental health consequences of the COVID-19 pandemic has been characterized by the coordinated implementation of mental health plans, ranging from a health sectoral initiative to inter-agency and intersectoral efforts. However, it is imperative that increased funding is allocated to mental health, and efforts should be made to promote the participation of people with lived experiences and communities in the design and implementation of the proposed actions. This aspect could be of key importance to social peace and community recovery after the pandemic.